Salivary IgA levels and infection risk in elite swimmers - Gleeson, M.; McDonald, W. A.; Pyne, D. B.; Cripps, A. W.; Francis, J. L.; Fricker, P. A.; Clancy, R. L. (Medicine & Science in Sports & Exercise, 1999)
The purpose of this study was to assess the relationship between changes in salivary IgA and training volume, psychological stress, and infection rates in a cohort of 26 elite swimmers over a 7-month training period and to compare the changes with a group of 12 moderately exercising controls. The results indicate that measurement of salivary IgA levels over a training season may be predictive for athletes at risk of infection.